2017
DOI: 10.1134/s1607672917020120
|View full text |Cite
|
Sign up to set email alerts
|

Possible mechanism of bursting suppression in nociceptive neurons

Abstract: The use of the mathematical model of rat nociceptive neuron membrane allowed us to predict a new mechanism of suppression of ectopic bursting discharges, which arise in neurons of dorsal root ganglia and are one of the causes of neuropathic pain. The treatment with comenic acid leads to switching off the ectopic bursting discharges due to a decrease in the effective charge transferring via the activation gating structure of the slow sodium channels (Na 1.8a). Comenic acid is a drug substance of a new non-opioi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
10
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(10 citation statements)
references
References 7 publications
0
10
0
Order By: Relevance
“…According to the outcomes of previous studies, ordinary pain can be simulated by a constant input current [52, 54]. Figure 3 showed the behavior of the TG block to a common pain (i.e., constant current).…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…According to the outcomes of previous studies, ordinary pain can be simulated by a constant input current [52, 54]. Figure 3 showed the behavior of the TG block to a common pain (i.e., constant current).…”
Section: Resultsmentioning
confidence: 99%
“…It has been shown that some ion channels, such as the Na v 1.8 slow sodium channels, play a role in pain pathway and pain intensity modification. In this regard, their synthesis and activity may also cause different neuronal potential and behavior [52]. The HH model has the capability to model and describe the effect of diverse factors influencing the ion channels.…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations